Estimated analysis criteria of hatched weight and body weight 12 weeks of Kampung chicken selection - Fitra Aji Pamungkas (Indonesian Center for Animal Research and Development (ICARD), 2005)
Genetic parameter estimation for production traits are important in designing genetic selection program for Kampung chicken. The aimed of this research is to study heritability, accuracy of selection, and phenotypic and genotypic correlation of hatched weight and body weight at 12 weeks of Kampung chicken. Five hundred and fourteen head of Kampung chicken consist of 13 cocks, 65 hens, and 436 chicks were used in this study. Nested design analysis were used as described by Becker. The heritability estimation of hatched weight was calculated based on paternal half-sib, maternal half-sib, and full-sib corelation and it’s values were 0.35, 0.37, and 0.36 respectively. Heritability of body weight at 12 weeks based on paternal half-sib, maternal half-sib, and full-sib corelation were 0.27, 0.18, and 0.22 respectively. Selection accuracy of hatched weight were 59-61%, and selection accuracy of body weight at 12 weeks were 42 up to 52%. Genotypic and phenotypic correlation of hatched weight and body weight at 12 weeks estimation based on paternal half-sib, maternal half-sib, full-sib corelation were 0.29, 0.78, 0.51, and 0.17 respectively, indicated selection on one trait will affected the response on other traits positively. Key Words: Heritability, Selection, Kampung Chicken